An optimization study on the excess reactivity in a linear breed-and-burn fast reactor (B&BR). (August 2016) - Hartanto, Donny; Kim, Chihyung; Kim, Yonghee
Highlights: A small B&BR core design adopting vented annular metallic fuel is presented.Excess reactivity can be reduced below 1 via Zr-zoning in the metallic fuels.A Zr-zoned and pan-shaped core leads to a small excess reactivity and long lifetime.The radial power profile is also flattened by the Zr-zoning. Abstract: This work is concerned with minimization of the excess reactivity in a compact linear breed-and-burn fast reactor (B&BR). Neutronic studies are performed to reduce the core excess reactivity below 1 in order to prevent possibility of the prompt criticality accident. A reference B&BR core design is introduced as a starting point for the optimization, which is loaded with vented annular metallic (U–Zr) fuels. The initial criticality of the B&BR core is achieved by using an LEU (low-enriched U) fuel and a spent nuclear fuel is reutilized as the blanket fuels. In order to minimize the transitional excess reactivity of the B&BR core, this study proposes a splitting of the Zr content in the U–Zr metallic fuel in combination with a geometrical optimization of the initial LEU core to flatten the radial power distribution simultaneously. A Zr-zoning is first applied to the initial LEU core to reduce excess reactivity and then a concave initial LEU core is also adopted to achieve both small excess reactivity and long lifetime of the B&BR core. In addition, a similar Zr-zoning strategy is also applied to the blanket region to optimize the excess reactivity behavior and flatten the radial power as well. It is demonstrated that a Zr-zoning combined with a concave core configuration can provides a promising neutronic performances. Finally, a recommended core has been characterized in terms of the burnup reactivity change, conversion ratio, power profiles, and reactivity coefficients.